Pembentukan Kader Kesehatan Remaja Berbasis Trias UKS Menuju Indonesia Emas 2045 di SMK Pangudi Luhur Tarcicius Semarang - Yulia Nur Khayati; Vistra Veftisia; Ari Widyaningsih; Moneca Diah Listiyaningsih (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2026)
Adolescents are a strategic group in human resource development towards Indonesia Emas 2045. However, there is still a need to strengthen adolescent health education in schools, especially in non-health schools. This community service activity aims to develop adolescent health cadres based on the Trias UKS (Healthy Child Health Program) at SMK Pangudi Luhur Tarcicius Semarang and increase students' knowledge about adolescent health. The implementation method consisted of preparation, cadre recruitment, module development, training, implementation, mentoring, evaluation, and development of a sustainability plan. Evaluation was conducted using pre- and post-tests with 30 participants. The results of the activity indicated that all stages of the service had been completed. Knowledge scores increased from 12.67 to 13.73, indicating a significant difference between pre- and post-activity scores. The formation of adolescent health cadres based on the Trias UKS has proven beneficial in increasing student knowledge and strengthening their role as health promotion agents in schools. This program needs to be continued through UKS coaching, regular cadre development, and mentoring from supervising teachers.   ABSTRAK Remaja merupakan kelompok strategis dalam pembangunan sumber daya manusia menuju Indonesia Emas 2045. Namun, masih terdapat kebutuhan penguatan pendidikan kesehatan remaja di lingkungan sekolah, terutama pada sekolah non-kesehatan. Kegiatan pengabdian kepada masyarakat ini bertujuan membentuk kader kesehatan remaja berbasis Trias UKS di SMK Pangudi Luhur Tarcicius Semarang serta meningkatkan pengetahuan siswa mengenai kesehatan remaja. Metode pelaksanaan terdiri atas tahap persiapan, rekrutmen kader, penyusunan modul, pelatihan, implementasi, pendampingan, evaluasi, dan penyusunan rencana keberlanjutan. Evaluasi dilakukan menggunakan pre-test dan post-test terhadap 30 peserta. Hasil kegiatan menunjukkan bahwa seluruh tahapan pengabdian telah terlaksana. Skor pengetahuan meningkat dari 12,67 menjadi 13,73 terdapat perbedaan bermakna antara skor sebelum dan sesudah kegiatan. Pembentukan kader kesehatan remaja berbasis Trias UKS terbukti bermanfaat dalam meningkatkan pengetahuan siswa dan memperkuat peran siswa sebagai agen promosi kesehatan di sekolah. Program ini perlu dilanjutkan melalui pembinaan UKS, kaderisasi berkala, dan pendampingan guru pembina.